The Effect of Online Application Use on Student Academic Achievement in Higher Education - Khoirul Fadhil; Susi Herawati; Rizki Pebrina; Adam Mudinillah (Yayasan Adra Karima Hubbi, 2024)
The aim of this study is to analyse the impact of Online Application Use on Student Academic Performance in Colleges using E-Learning and Whatspad. The use of E-learning and WhatsApp as online learning platforms is increasingly applied. E-learning offers flexibility in time and place of study, as well as easy and fast access to information. WhatsApp, on the other hand, enables easy and quick communication between students, lecturers, and learning groups. The study aims to analyze the impact of the use of E-Learning and WhatsApp on student academic achievement in colleges. The survey method was carried out on 200 students from various majors at Mahmud Yunus Batusangkar State Islamic University (UIN). Data was collected through questionnaires that measured the intensity of E-learning and WhatsApp usage, as well as student academic achievement. Research results show that the intensity of E-learning and WhatsApp use by students is high. Descriptive statistical analysis showed that the average student IPK was 3.52 with a standard deviation of 0.48. The average E-learning intensity was 3.2 hours per day with the standard 1.2 hour deviation, while the average WhatsApp usage intensity is 2.8 hours a day with an standard 1.1 hours deviation. Correlation analysis shows a significant positive correlation between the intensity of E-learning usage and student academic achievement (r = 0.52, p < 0.01). This suggests that the higher the use intensity, the higher also the student's academic performance. Significant positive relationship was also found between WhatsApp intensity and students' academic accomplishment (r=0.48, p<0.01). This indicates that the greater the intensities of WhatsApp use, the larger are the student's academical achievements. The study concluded that the use of E-learning and WhatsApp proved to have a significant positive impact on student academic achievement. These online platforms can help students improve their learning outcomes by providing easy access to information, flexibility in time and place of study, and effective communication.